Advances in Natural Biopolymer‐Based Electrolytes and Separators for Battery Applications. (11th October 2020) - Lizundia, Erlantz; Kundu, Dipan
Abstract: Rechargeable batteries are ubiquitous, and their usage is projected to grow tremendously over the years. They are vital to curbing the fossil fuel dependency and are destined to play a significant role in the future energy landscape. However, rising demand will eventually strain raw material resources, and potentially cripple the development and deployment of associated technologies. In this regard, alongside materials and methods involving sustainable resources, greener manufacturing and recycling potential, renewable resource derived biodegradable materials, i.e., natural biopolymers–are attracting interest for sustainable and eco‐friendly future batteries. While they are being studied for nearly all aspects of a battery cell development, their exploration as an electrolyte component has been the subject of widespread investigations. These studies include, but are not limited to, their utilization as the building block for electrolyte wettable and more thermally resistant separators, as an alternative to synthetic polymers in gel polymer and solid polymer electrolytes, and as functional membranes to inhibit the loss of electroactive species in diverse battery chemistries. Here, a summary of natural biopolymer‐based electrolytes and separators development that incorporate novel concepts is presented to tackle specific issues in various battery systems and future perspective underpinning their further advancement. Abstract : The use of natural biopolymers as electrolytes and separators for battery applications is critically investigated. Their role beyond classic porosity and ionic conductivity studies is highlighted, demonstrating the unignorable advantages provided by renewable resources in the energy storage field.